Polímeros fluorados anfifílicos para aplicação em diagnósticos por imagens de ressonância magnética - Muraro, Paulo Isaias Rossato (2014)
The goal of this study is to present kinetic studies of (co)polymerization as well as the synthesis and characterization of amphiphilic copolymers with a fluorinated segment. Copolymers were obtained by RAFT (co)polymerizations using one-pot and miniemulsion methods. Different monomers were used to obtain stable selforganized systems, being that one of them was always fluorinated. The resulting copolymers showed different properties, especially when evaluating their selforganization. For this reason, different methodologies for self-organization were used, depending on the synthetic route by which the copolymers were obtained. The self-organization systems formed by the fluorinated amphiphilic copolymers were analyzed by dynamic light scattering (DLS) to determine the size and distribution of the species. The micellar systems analyzed showed great potential for the use in diagnostic imaging, which makes it possible to identify the presence of fluorine in the interior of the micelles through 19F NMR analysis. Relaxation times T1 were measured and values were similar to those reported in the literature. To reinforce the above statement, we performed cell viability assays, which demonstrated the biocompatibility of fluorinated amphiphilic copolymers.